نحو مفهوم واضح للبنية السيميائية اللسانية للنص الثقافي - منصور الصقر, غضاب (قــــــراءات; No 09 (2016): مجلة قراءات, 2019)
يهدف هذا البحث إلى دراسة البنية السيميائية اللسانية للنص الثقافي، من خلال تبيان مفهوم الثقافة من حيث توظيفها، ومقابلتها للاثقافة، وتوضيح مفهومها السيميائي، ومدارسها، وأعلامها، وبنيتها، وديناميتها، والإشارة إلى علاقتها بنسق اللغة الطبيعية، وبنحو الأشكال الرمزية، وتبيان مفهوم النص الثقافي، وعلاقته بالعلامة، والوظيفة، والمرسل والمستقبل، والنصوص أخرى. لقد كشف البحث أنَّ النصَّ الثقافي هو الوحدة الدالة التي تتشكل منها الثقافة، وهو كل رسالة تؤدي وظيفة نصية في ثقافة معينة. ويتكوَّن من مجموعة من الأنساق الدلالية التداولية، على نحو اللغات الطبيعية، واللغات الاصطناعية، والأساطير، والفنون، والموسيقى. وتحتل اللغة الطبيعية مكانة متميزة في بنية الثقافة؛ إذ تُعَدُّ النسق الأول في الثقافة البشرية، والنسق السيميائي الخالص، الذي يعطينا فكرة واضحة عن وظيفة العلامة. الملخص باللغة الإنجليزية: Towards a clear concept of the Semiolinguistic structure of cultural text By Dr. Ghassab Mansoor Al Saqr This research aims to study the semiolinguistic structure of cultural text, through a statement of the concept of culture in terms of usage as opposed to, non culture, and a clarification of the concept of semiotics, its schools, figures, structures and dynamics. It also aims to make reference to its relationship to natural language systems, and symbolic forms of syntax, and demonstrate the concept of cultural text, its relationship to the sign, function, the sender and the receiver, besides other texts. The research has revealed that the cultural text is a functional unit that makes up the culture, which refers to any text message which leads to a textual fonction in a particular culture. It consists of a set of Semantic and Pragmatic systems, as natural language, artificial language, mythology, arts, and music. Natural language occupies a privileged position in the structure of culture; it is the first system in human culture, and pure semiotic system, which gives us a clear idea about the function of the sign.